2010
DOI: 10.3748/wjg.v16.i13.1676
|View full text |Cite
|
Sign up to set email alerts
|

Peeling a giant ileal lipoma with endoscopic unroofing and submucosal dissection

Abstract: Lipoma is relatively common in the colon but is less often in the small intestine. Most lipomas are incidentally detected at endoscopy and are usually small and asymptomatic. However, some of them can present with obstruction and/or intussusceptions. Surgical resection is commonly recommended to remove such significant lipomas with a limited pedicle and larger than 2 cm in size, as endoscopic resection may result in unfavorable complications such as intestinal perforations. We report a case of 62-year-old man … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 16 publications
0
20
0
1
Order By: Relevance
“…Surgical resection, including laparoscopic surgery, is a common treatment for lipomas of the small bowel [16]. A PubMed search for the last 10 years yielded only 2 reports of patients with lipomas in the small intestine treated with endoscopic resection; one was a giant ileal lipoma treated with endoscopic unroofing submucosal dissection [11], and the other was a lipoma of the jejunum removed by endoscopic resection using an SB knife. To our knowledge, no report of ESD for ileal lipoma has been published, although Sugimoto et al [13] reported a case with an ileal adenoma removed with ESD after total colectomy due to familial adenomatous polyposis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical resection, including laparoscopic surgery, is a common treatment for lipomas of the small bowel [16]. A PubMed search for the last 10 years yielded only 2 reports of patients with lipomas in the small intestine treated with endoscopic resection; one was a giant ileal lipoma treated with endoscopic unroofing submucosal dissection [11], and the other was a lipoma of the jejunum removed by endoscopic resection using an SB knife. To our knowledge, no report of ESD for ileal lipoma has been published, although Sugimoto et al [13] reported a case with an ileal adenoma removed with ESD after total colectomy due to familial adenomatous polyposis.…”
Section: Discussionmentioning
confidence: 99%
“…However, lipoma treatment is required when a lipoma is difficult to distinguish from other malignant tumors or when patients complain of symptoms [6, 7]. Most cases of symptomatic lipomas in the small bowels are treated with surgical resection [8, 9, 10], but a few cases are treated with endoscopic resection because of technological advances in endoscopic procedures and equipment [11, 12]. Endoscopic submucosal dissection (ESD) has recently been developed for en bloc resection of gastric and colonic neoplastic tumors [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…The main limitation is that retrieval of the specimen may not be possible. [5,6] Both these techniques are time-consuming. Endoscopic snare polypectomy of a large lesion in the small intestine is more challenging due to narrower lumen.…”
Section: Discussionmentioning
confidence: 99%
“…Asymptomatic lipomas do not require any treatment. Symptomatic gastrointestinal lipomas could be removed endoscopically by means of snare polypectomy (5,6,17,18,23,(26)(27)(28)(29)(30) or by endoscopic submucosal dissection (31)(32)(33). Preventive submucosal injection (saline or epinephrine), clipping of a lipoma base and the use of detachable nylon or polyglactin loop could reduce the risk of complications such as bleeding or perforation (28,(34)(35)(36)(37)(38)(39).…”
Section: Therapeutic Optionsmentioning
confidence: 99%